2013
DOI: 10.1016/j.paid.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese adaptation of the Gudjonsson Suggestibility Scales (GSS1 and GSS2): Empirical findings

Abstract: In study 1 (n = 51, M age = 21.4 years, SD = 5.7), the validity of the Portuguese adaptation of the Gudjonsson Suggestibility Scales (Pires, 2011) was shown through the comparison of means of the original (Gudjonsson, 1997) and the translated scales and the analysis of the correlations between the GSS1 and GSS2 scores. The relationships between interrogative suggestibility and the big five were also addressed and the results point to independence between suggestibility and personality, which is in line with Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(25 reference statements)
3
2
0
1
Order By: Relevance
“…This prediction (hypothesis 1) was not confirmed, pointing to independence between suggestibility and psychological maladjustment. These results are in line with aforementioned findings (Leibman et al, 2002;Pires et al, 2013;Polczyk, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This prediction (hypothesis 1) was not confirmed, pointing to independence between suggestibility and psychological maladjustment. These results are in line with aforementioned findings (Leibman et al, 2002;Pires et al, 2013;Polczyk, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…In a psychiatric sample, Wolfradt and Meyer (1998) also found that suggestibility correlated positively with anxiety. Although these findings support the theoretical model of Gudjonsson and Clark, there are also studies that point to independence between suggestibility and anxiety in normal samples (Pires, Silva, & Ferreira, 2013;Polczyk, 2005).…”
Section: Introductionsupporting
confidence: 47%
“…In a German translation of the GSS 1 (Gubi-Kelm and Schmidt, 2019), women achieved higher immediate recall rates for the details of the GSS story than men. Other GSS 1 studies did not reveal evidence of any significantly different suggestibility scores across gender (Gudjonsson, 1997(Gudjonsson, , 2003Gorassini et al, 2006;Pires et al, 2013). Most previous GSS studies investigated student samples (Gorassini et al, 2006;Reutemann, 2006;vom Schemm et al, 2006;Gubi-Kelm and Schmidt, 2018).…”
Section: Structure Of the Gssmentioning
confidence: 93%
“…The interview-based original and standard versions of the GSS have been translated from English into several languages including Icelandic (Haraldsson, 1985), Dutch (Smeets et al, 2009), Polish (Polczyk, 2005), Portuguese (Pires et al, 2013), andGerman (vom Schemm et al, 2006;Gubi-Kelm and Schmidt, 2018) versions of the GSS 1 and Polish (Polczyk, 2005), Japanese (Watanabe et al, 2013), Portuguese (Pires et al, 2013), Italian (Vagni et al, 2015), and German (Wolfradt and Kugener, 1998) versions of the GSS 2. The translated versions have been typically tested in a participant-experimenter interaction in samples smaller than 210 participants.…”
Section: Introductionmentioning
confidence: 99%
“…Gudjonsson (GSS 1). As Escalas de Sugestionabilidade construídas por Gudjonsson (1984aGudjonsson ( , 1997 apenas recentemente foram adaptadas para a população portuguesa (Pires, 2011;Pires, Silva, & Ferreira, 2013). No presente estudo foi aplicada uma versão da GSS 1 adaptada por Capelo, Cruz, Freitas, Furtado, Pinto, Rebelo e Pinho, em 2008, para fins de investigação na Faculdade de Psicologia e de Ciências da Educação da Universidade de Coimbra.…”
Section: Materiaisunclassified